Analisis Gaya Bahasa dan Makna Lirik pada Lagu Dua Bilah Mata Pedang Album Banal Semakin Binal - Ahmad Sayyid Iqbal Bangbang Barnas; Askurifa'i Baksin (UNISBA Press, 2023)
Abstract. This research is based on the research context that occurred in The Jansen Band due to the explosion of the Jansen's new album which was released in 2022 and immediately attracted the attention of music lovers in Indonesia. Even the music from The Jansen band is much loved by young people. This causes a unique music with a mid tempo punk genre but can be accepted and pleasant to listen to anywhere. Therefore, an in-depth analysis will be carried out on the style of language used and the meaning of the lyrics contained in the band The Jansen's album entitled